ESTIMASI PARAMETER DAN UJI HIPOTESIS PADA MODEL LINEAR MULTIVARIAT DENGAN METODE LDL - Makkulau Makkulau; Susanti Linuwih; Purhadi Purhadi; Muhammad Mashuri; Rahmawati Pane (LPPM Universitas Terbuka, 2010)
Outliers are observations (data) that lies in an abnormal distance from other observations. Outliers can be distinguished into outliers of univariate or multivariate observation and outliers of univariate or multivariate linear models. Multivariate linear model is a linear model with more than one dependent (response) variables. This research studied parameter estimation and hypothesis test for multivariate linear model using Likelihood Displacement Statistic-Lagrange Method called as LDL method for detecting outlier observations in multivariate linear models with the LDLAm statistical test.